Changes in Stratospheric Transport and Mixing During Sudden Stratospheric Warmings - Cámara, Álvaro de la; Abalos, Marta; Hitchcock, Peter B. (Journal of Geophysical Research: Atmospheres, 2018)
The extreme disruptions of the wintertime stratospheric circulation during sudden stratospheric warmings (SSW) have large effects on tracer concentrations through alterations in transport. This study analyzes the changes in residual circulation and isentropic mixing associated with SSWs, by performing composites using reanalysis (European Centre for Medium‐Range Weather Forecasts Re‐Analysis Interim) and simulations of the Whole Atmosphere Community Climate Model. The advective Brewer‐Dobson circulation accelerates around 15 days prior to the wind reversal at 60°N, 10 hPa during the onset of SSWs. Soon afterward, it decelerates, leading to reduced advective transport into the vortex and descent over the pole, which persist for more than 2 months below 30 hPa. The isentropic mixing has a distinct signature in altitude: It is enhanced at the central date of the SSW in the midstratosphere (about 10 hPa or 800 K), and this signal is delayed and more persistent at lower altitudes. It is shown that sufficiently deep SSWs (particularly those related to Polar‐night Jet Oscillation events) have a stronger response in the Brewer‐Dobson circulation and mixing. In particular, both the polar downwelling and the tropical upwelling are anomalously weak in the lower stratosphere for 90 days after the onset of Polar‐night Jet Oscillation events. The redistribution of potential vorticity during the life cycle of SSWs is discussed due to its relevance for the stratospheric circulation. It is shown that the diffusive flux of potential vorticity, calculated in equivalent latitude coordinates, remains anomalously high in the lower stratosphere, a feature that is not seen in more conventional advective eddy fluxes across latitude circles. A. de la Cámara has been supported by the Advanced Study Program at The National Center for Atmospheric Research (NCAR), which is sponsored by the U.S. National Science Foundation and by the Spanish project PALEOSTRAT (CGL2015-69699). M. Abalos has been supported by the NASA ACMAP program and by ...